Study on the mechanical lifting process for membrane fouling control. Issue 17 (22nd November 2017) - Chen, Qianqian; Liu, Zhiyu; Lu, Xiaolong; Ma, Zhong
ABSTRACT: In order to reduce energy consumption and control membrane fouling, a novel submerged membrane separation process was developed in this paper. In this design, the traditional aeration device was replaced by a low-power motor. Through the traction force produced by the motor, the membrane module can move up and down in the water. In this case, friction will be created between the membrane surface and the water, which can prevent the deposition of pollutants on the membrane surfaces and then control membrane fouling. After a 64-min filtration operation, compared with the aeration process, the cake-layer resistance of the lifting process reduced by about 13.6%. For a 120-min filtration operation, the transmembrane pressure ( TMP ) of the lifting process was 11.1% lower than that of the aeration process at the end of filtration. According to the long-time operation, the stable running time was increased from 352 min of the aeration process to 408 min of the lifting process. All these suggest that the novel lifting process can control membrane fouling more effectively than the aeration process. Therefore, the lifting process is an efficient and feasible membrane separation technology.